Digital Humanities in Architecture: Towards a Deeper Understanding of Space - Al-Kadhim, Ahmed; Al-Tameemi, Osamah; Abdullah, Suhail (Technium: Romanian Journal of Applied Sciences and Technology, 2025)
The primary objective of this research is to elucidate how digital humanities can enhance the understanding of architectural space. It is important to underscore the significance of this study, as it applies digital tools and modern technologies to the field of architecture with the aim of interpreting and comprehending spaces for optimal efficiency. The research is carried out adopting a qualitative analytical approach, collecting and analyzing data by the use of 3D models of certain urban spaces and buildings, with a view to offering more detailed insights on the architectural configuration. The literature review section provides insights into the architecture of digital humanities, along with an examination of previous research and relevant theories in this domain. The research methodology outlines the tools utilized, the sample selection, and the data collection processes. Data analysis involves the use of content and contextual analysis tools to draw conclusions. The findings suggest that the application of digital humanities contributes to expanding knowledge, fostering creativity, and offering new perspectives in architectural design thinking, particularly for socially responsible sustainable cities. Finally, the study compares the findings with other research and analyzes them in relation to existing theories, highlighting new contributions to science and potential practical benefits. The study concludes with suggestions and recommendations for future research, emphasizing the continued integration of digital technology in architectural design for spatial analysis and understanding.